2011
DOI: 10.1007/s11095-011-0644-x
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Two Modes of Non-isothermal Crystallization of Glasses Produced by Milling

Abstract: The two modes of crystallization of organic glasses is a result of the combined effects of faster surface crystallization and variation in specific surface area by milling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 37 publications
2
41
0
Order By: Relevance
“…DSC studies have revealed the atypical bimodal crystallization of milled amorphous griseofulvin wherein the first exotherm occur prior to the T g (Trasi and Byrn 2012;Trasi et al 2010;Willart et al 2012). Such behavior was also noticed for other milled amorphous form of felodipine, sulfamerazine, piroxicam, hydrochlorothiazide (Chattoraj et al 2012). Interestingly, the first crystallization event originates from surface that is followed by bulk process beyond T g .…”
Section: Crystallization Melting Crystallinity and Mixing Interactmentioning
confidence: 80%
“…DSC studies have revealed the atypical bimodal crystallization of milled amorphous griseofulvin wherein the first exotherm occur prior to the T g (Trasi and Byrn 2012;Trasi et al 2010;Willart et al 2012). Such behavior was also noticed for other milled amorphous form of felodipine, sulfamerazine, piroxicam, hydrochlorothiazide (Chattoraj et al 2012). Interestingly, the first crystallization event originates from surface that is followed by bulk process beyond T g .…”
Section: Crystallization Melting Crystallinity and Mixing Interactmentioning
confidence: 80%
“…DSC studies have revealed the atypical bimodal crystallization of milled amorphous griseofulvin wherein the first exotherm occur prior to the T g (Trasi and Byrn 2012;Trasi et al 2010;Willart et al 2012). Such behavior was also noticed for other milled amorphous form of felodipine, sulfamerazine, piroxicam, hydrochlorothiazide (Chattoraj et al 2012). Interestingly, the first crystallization event originates from surface that is followed by bulk process beyond T g .…”
Section: Crystallization Melting Crystallinity and Mixing Interactmentioning
confidence: 90%
“…Upon using lower heating rates, the latter can potentially be overshadowed by the surface crystallization exotherm. In addition, reducing the heating rate for compounds with low surface growth rates can also result in exhibiting a crystallization exotherm around T g , to the extent that the heating rate used allows detectable crystallization to take place (39). The faster the surface growth rate, the harder it will be to prevent its crystallization at T g by increasing the heating rate in the experiment.…”
Section: Discussionmentioning
confidence: 99%